Can European businesses achieve productivity gains from investments in energy efficiency? - Fotios Kalantzis; Hanna Niczyporuk (European Investment Bank (EIB), 2021)
Energy efficiency investments are essential for transitioning to a carbon-neutral economy. Nevertheless, despite being financially viable, many energy efficiency investment opportunities do not materialise. The existing literature attributes this situation to financial and non-financial factors. Research suggests that many firms focus only on direct energy savings and neglect non-energy benefits that include increased labour productivity. Up to date, due to lack of high-quality data, few studies attempted to quantify the effects of the energy efficiency investments on firm-level outcomes other than the reductions in energy consumption. This paper overcomes this barrier by using novel data from a firm-level survey conducted by the European Investment Bank that covers more than 15,000 firms in 27 European Union member states and the UK during 2018-2019. It studies the relationship between the energy efficiency investment and the labour productivity of the European firms, utilising instrumental variables methodology to account for potential endogeneity. The results show a positive and causal relationship between energy efficiency investment and labour productivity. The findings of the paper suggest that firms can benefit much more from the energy efficiency investment than what is often assumed, and highlight a need for government policies that would increase firms' awareness of the non-energy benefits.
Keywords: 330; Energy Efficiency; Climate Investment; Productivity